2012
DOI: 10.1002/zaac.201200114
|View full text |Cite
|
Sign up to set email alerts
|

The Zintl Phases Eu3Mg5Si5 and Eu3Mg5Ge5

Abstract: The Zintl phases Eu 3 Mg 5 Si 5 and Eu 3 Mg 5 Ge 5 were synthesized by high-frequency melting of the elements in sealed tantalum tubes. Both of their structures have been refined from X-ray single crystal diffractometer data:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The structural complexity and the simple surprise continue to make Zintl clusters and their near relatives a source of fascination and interest. New Zintls of the Sr 12 Mg 17.8 Li 2.2 Si 20 type, Eu 3 Mg 5 E 5 (E = Si or Ge) have been reported from the reaction of the elements 69 and the neutral Zintl Ge 9 {Si(SiMe 3 )} 3 SnPh 3 from the reaction of Ph 3 SnCl and the previously reported K[Ge 9 {Si(SiMe 3 )} 3 ]. The substitution of Zintl anions by reaction of the parent Ge 9 4À or derivatives with cationic species has never before been used to prepare such a tetrasubstituted neutral species.…”
Section: Annual Reports a Reviewmentioning
confidence: 70%
“…The structural complexity and the simple surprise continue to make Zintl clusters and their near relatives a source of fascination and interest. New Zintls of the Sr 12 Mg 17.8 Li 2.2 Si 20 type, Eu 3 Mg 5 E 5 (E = Si or Ge) have been reported from the reaction of the elements 69 and the neutral Zintl Ge 9 {Si(SiMe 3 )} 3 SnPh 3 from the reaction of Ph 3 SnCl and the previously reported K[Ge 9 {Si(SiMe 3 )} 3 ]. The substitution of Zintl anions by reaction of the parent Ge 9 4À or derivatives with cationic species has never before been used to prepare such a tetrasubstituted neutral species.…”
Section: Annual Reports a Reviewmentioning
confidence: 70%
“…Nevertheless, the compound is one electron deficient according to the Zintl–Klemm concept although, surprisingly, LMTO band structure calculations indicated that the bonding is fully optimized within the anionic substructure. The trimeric unit Ge 3 8– is observed in the electron precise Eu 3 Mg 5 Ge 5 24 as well as in the electron deficient Sr 12 Mg 17.9 Li 2.1 Ge 20 ,25 coexisting with isolated Ge 4– in both cases. The linear Ge 5 12– pentamer has been elusive so far, but is expected in the n = 5 member of the homologous series to represent the missing link between the Ge 4 10– four‐ and Ge 6 14– six‐membered chains.…”
Section: Introductionmentioning
confidence: 91%
“…The quantitative synthesis of corresponding Ca/(Li,Mg)/Ge phases was also challenging. [10][11][12] As their structures are so closely related, it is difficult to distinguish the homologous structures between each other or with their parent-structures from X-ray powder diffraction patterns. Therefore, the characterization of our structures is limited essentially to single crystal diffraction and qualitative chemical composition by EDS.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…These AE/M/Tt systems were intensively investigated by Nesper and co-workers. [10][11][12] Previously, the complete replacement of small polarizing Li by Ag in the Ca-M-Ge germanide systems resulted in a new series of structures, Ca 2+n M 2+z Ge 2+n−z (M = Ag, Mg), which are built up by linear intergrowth of slabs cut from the parent structures, CaM 1+z Ge 1−z (AlB 2 or TiNiSi type) and CaGe (CrB type). [13][14][15][16] Our next attempt was toward similar isovalent replacement of Mg by divalent TM elements like Mn and Cd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation